Evaluating Storage and Effective Moduli of In Situ Polymerised and Melt Extruded PA6 Graphite (G) Composites. - Muneer Umar; Michael Ikpi Ofem; Auwal Sani Anwar; Muhammad Murtala Usman (Journal of Mechanical Engineering Science and Technology (JMEST), 2021)
Four  PA6/graphite  (G)  composites  systems  were  made.  Two  using  in  situ  polymerisation  equivalent  in mixing strain and two systems melt extrusion of equivalent processing strain. The effective modulus of the carbons, room temperature storage modulus and storage modulus  at  80⁰C  were  evaluated.  The composite/unfilled PA6 ratios at E25 and that at E80 for the in situ polymerised system IG 40/10 are 1.37 and  1.63,  respectively.  For  the  in  situ  polymerised  system  IG  20/20,  the  same  were  1.96  and  2.28, respectively. For the melt-extruded systems, G 100/6 had the best E25 ratio of 1.67 and E80 of 2.03, whereas the same for G 200/3 system were respectively 1.87 and 2.64. While the better storage modulus properties exhibited by IG 20/20 in the in situ polymerised system is associated with a better filler connectivity network that enhanced heat dissipation. The better values shown in the G 200/3 melt-extruded system is associated with the lesser extrusion, which significantly reduced the tendency to thermal decay. Effective modulus for the in situ polymerised systems IG 40/10 and IG 20/20 were 7.5GPa and 8.9GPa while that of melt-extruded systems G200/3 and G100/6 tallied at 8.2 GPa.